2012
DOI: 10.1186/1743-422x-9-126
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Hepatitis C virus proteins with pattern recognition receptors

Abstract: Hepatitis C virus (HCV) is an important human pathogen that causes acute and chronic hepatitis, cirrhosis and hepatocellular carcinoma worldwide. This positive stranded RNA virus is extremely efficient in establishing persistent infection by escaping immune detection or hindering the host immune responses. Recent studies have discovered two important signaling pathways that activate the host innate immunity against viral infection. One of these pathways utilizes members of Toll-like receptor (TLR) family and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 87 publications
0
39
0
1
Order By: Relevance
“…In addition, siRNA-targeting ATGs, that inhibit autophagy, abrogates HCV replication [69] . Moreover, HCV infection activates various pattern recognition [70] , being able to trigger autophagy [71] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, siRNA-targeting ATGs, that inhibit autophagy, abrogates HCV replication [69] . Moreover, HCV infection activates various pattern recognition [70] , being able to trigger autophagy [71] .…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that HCV interferes with TLR signaling pathway via interaction with their signaling intermediates (16, 18) or altering their expression levels (10, 12). The data presented in this study indicated that HCV downregulats the expression of TLR3 in PBMC of patients with HCV-infected chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…TRIF overexpression mice are less susceptible to encephalomyocarditis virus (EMCV) infection, have a significantly lower viral load in the heart . Non structural 3/4 A protein of hepatitis C virus (HCV) disrupts TLR3 and RIG-I signaling pathways by cleaving TRIF and IPS-1 (IFN-b promoter stimulator 1), thus halting the defense against HCV (Imran et al, 2012).…”
Section: Discussionmentioning
confidence: 99%